Hematochezia caused by tandospirone in a patient with major depressive disorder and anxious distress: a case report - Jiang, Xingmei; Ma, Zhongrui; Li, Zhixiong; Ou, Ying; Luo, Zhenhua; Li, Zhe (Frontiers in Psychiatry, 2023)
Background Major depressive disorder (MDD) with anxious distress is a relatively common condition that is often associated with a poor treatment response. In order to enhance the effectiveness of MDD treatment, 5-HT1A agonists like tandospirone are often prescribed in conjunction with antidepressants. While it is known that antidepressants can increase the risk of bleeding, whether tandospirone poses a similar risk remains uncertain. Case presentation We presented the case of a 55-year-old Chinese woman diagnosed with MDD and anxious distress. After receiving various types of antidepressants, she experienced hematochezia following the administration of tandospirone, sertraline, and agomelatine. The occurrence of hematochezia ceased after tandospirone was discontinued. The patient was subsequently discharged with a treatment regime consisting of sertraline and agomelatine. During the 1-month follow-up, she reported no hematochezia. Conclusion Tandospirone may potentially increase the risk of hematochezia in patients with MDD and anxious distress.